Study of physical parameters for efficient production of thermostable 50a protease using 2 l bioreactor - Nuramirah Azali (2013)
In this study, three physical parameters were selected to study its effect on the production of thermostable 50a protease and were then identified the optimal conditions of physical parameters. Selected parameters were incubation time, agitation rate and inoculum size. The effect of physical parameters to Thermostable 50a protease production was optimized by using the conventional method of one factor at a time (OFAT). Cultivation is done in a volume of 2 L bioreactor at constant conditions: temperature 37 ° C and pH 7 during the incubation. The first physical parameter studied was incubation time, followed by agitation rate and inoculum size. The ranges used were: incubation time (0 hours to 56 hours), agitation rate (0 rpm to 200 rpm) and inoculum size (2.5% to 10%). The optimized content of thermostable 50a protease was 233.222 Um1ˉ¹ and bacterial growth of 1.346 at optical density (OD) 450 nm were obtained with optimal parameters conditions: incubation time (46 hours), agitation rate (150 rpm) and inoculum size (2.5%). These results showed that, by knowing the optimal physical parameters condition, it will give advantages to produce high quantities of thermostable 50a protease and can reduce time consuming and also give it an edge on cost reduction, particularly in the industrial scale.